Image of contradiction: an approach to the novels of Henry Green - Holmesland, Oddvar (University of Edinburgh, 1983)
The novels of Henry Green (pseudonym of Henry Vincent Yorke) represent successive experiments in creating a visual artistic form, through authorial 'disengagement'. Green's method has gained him a reputation as one of the most elusive and enigmatic novelists in contemporary literature, whose moral purpose is extremely difficult to detect. This study proposes to overcome the critical impasse encountered by a conventional ap~roach to his fiction. It opposes the critical assumption that Green merely presents a picture of amorphous reality. It challenges the critical view that Green's images possess specific symbolic qualities that contain the novels' meaning. Rather, Green's images can only be analyzed as components of a self-contained artistic form with 'an everlasting life of its own'. As will be argued, Green's intention that this 'life' is to 'create life in the reader', entails a careful arrangement of visual images for the communication of certain values. The analysis of principles by which Green creates and juxtaposes images to produce 'tone' (i.e. attitude towards the scenes depicted) is paramount in this thesis. The introductory chapter reveals Green's affinity with Lawrence both celebrate sensual commitment to the living present. It denies claims that Green's Modernist apprehension of flux and fragmentation - reflected in analogies between the scenic design of his novels and abstract art, and in his progressive authorial 'disengagement' (comparable to T S Eliot's idea of 'impersonality') - discourages sensual participation, aligning his method with Eliot's compensatory contemplation of static perfection by the creation of an abstract, aesthetic pattern. The problem of tone is shown to be clarified by a critical model based on Sergei Eisenstein's theory of filmic montage, which incorporates principles of poetry and painting. Montage creates tone by accenting the incongruity of juxtaposed images, thereby evoking the appropriate emotive and intellectual response in the reader. Several chapters are devoted to the examination of tone in Green's novels. They demonstrate that only a montage-based approach can provide the key to understanding Green's fiction. The Conclusion synthesizes the main issues of the argument and expands on -previous comparisons drawn between Green and various critics and writers (contemporary and non-contemporary). It places Green's method within the perspective of Modernism and New Criticism. It furthermore argues that Green, despite his Modernist conception of a fragmentary world, is basically a Romantic. Like Coleridge and Keats, Green employs montage to integrate subject and object into a poetic, perceptual unity. Those of Green's novels possessing close thematic affinities are grouped together irrespective of the chronology of publication
The image of contradiction: an approach to the novels of Henry Green
Keywords: Literature; Mass; media; Performing; arts